2023
DOI: 10.3389/fpls.2023.1113535
|View full text |Cite
|
Sign up to set email alerts
|

Cultivars identification of oat (Avena sativa L.) seed via multispectral imaging analysis

Abstract: Cultivar identification plays an important role in ensuring the quality of oat production and the interests of producers. However, the traditional methods for discrimination of oat cultivars are generally destructive, time-consuming and complex. In this study, the feasibility of a rapid and nondestructive determination of cultivars of oat seeds was examined by using multispectral imaging combined with multivariate analysis. The principal component analysis (PCA), linear discrimination analysis (LDA) and suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 38 publications
0
5
0
1
Order By: Relevance
“…Utilizing this brief period for sowing forage crops could relieve the shortage by providing an alternative growing region, particularly during the winter and early spring seasons when livestock consumption demands are at their highest and the lower light intensity limits the growth of food crops (Xu et al, 2021). Oat ( Avena sativa L.) is one of the world's most cultivated cool‐season forage cereal crops and provides a vital source of livestock feed (Fu et al, 2023). The widespread popularity of oats as a source of high‐quality forage can largely be attributed to their tolerance to cold, drought, and barren soils (Usman et al, 2018), as well as their high forage yield, good nutritional value, palatability, and digestibility (Kanwal et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Utilizing this brief period for sowing forage crops could relieve the shortage by providing an alternative growing region, particularly during the winter and early spring seasons when livestock consumption demands are at their highest and the lower light intensity limits the growth of food crops (Xu et al, 2021). Oat ( Avena sativa L.) is one of the world's most cultivated cool‐season forage cereal crops and provides a vital source of livestock feed (Fu et al, 2023). The widespread popularity of oats as a source of high‐quality forage can largely be attributed to their tolerance to cold, drought, and barren soils (Usman et al, 2018), as well as their high forage yield, good nutritional value, palatability, and digestibility (Kanwal et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…sowing forage crops could relieve the shortage by providing an alternative growing region, particularly during the winter and early spring seasons when livestock consumption demands are at their highest and the lower light intensity limits the growth of food crops (Xu et al, 2021). Oat (Avena sativa L.) is one of the world's most cultivated cool-season forage cereal crops and provides a vital source of livestock feed (Fu et al, 2023).…”
mentioning
confidence: 99%
“…For example, feature filtering algorithms such as minimal joint mutual information maximization (JMIM) ( Kursa, 2018 ), information gain ( Zawadzki and Kosinski, 2019 ), and Gini impurity ( Bommert et al., 2020 ) have been shown to effectively reduce the dimensionality of high-dimensional data. However, current researches were mainly on individual datasets ( França-Silva et al., 2020 ; Fu et al., 2023 ), while little research has been reported on the use of feature filtering algorithms on multi-source fused data.…”
Section: Introductionmentioning
confidence: 99%
“…Oat is one of the world's most cultivated cool-season forage cereal crops and provides a vital source of livestock feed (Fu et al, 2023). In this issue, Yuan et al (2024) In semi-arid and arid areas in Northwest China, shrubs are grown to reduce soil erosion, combat desertification, provide ecological protection, and enhance livestock production.…”
mentioning
confidence: 99%
“…Oat is one of the world's most cultivated cool‐season forage cereal crops and provides a vital source of livestock feed (Fu et al, 2023). In this issue, Yuan et al (2024) studied variations of seed number and seed size in 23 oat ( Avena sativa L.) cultivars and concluded that the double‐seed spikelet number is a key ear characteristic when breeding high‐yielding cultivars.…”
mentioning
confidence: 99%